Validation of an Italian Questionnaire of Adherence to the Ketogenic Dietary Therapies: iKetoCheck - Lenycia de Cassya Lopes Neri; Monica Guglielmetti; Valentina De Giorgis; Ludovica Pasca; Martina Paola Zanaboni; Claudia Trentani; Elena Ballante; Serena Grumi; Cinzia Ferraris; Anna Tagliabue; on behalf of the KDTs Delphi Validation Study Group (Foods, 2023)
Ketogenic dietary therapies (KDTs) are an effective and safe non-pharmacological treatment for drug-resistant epilepsy, but adherence can be challenging for both patients and caregivers. In Europe, there are no adequate tools to measure it other than monitoring ketosis. This study aimed to adapt and validate the Brazilian adherence questionnaire, Keto-check, into the Italian version: iKetoCheck. Using the Delphi technique, 12 judges validated the contents through agreement rates and the Content Validity Index (CVI). The iKetocheck was self-completed electronically by 61 drug-resistant epilepsy or GLUT1 deficiency patients within an interval of 15 days to measure its reproducibility. The test–retest reliability was evaluated using Pearson’s correlation and relative significance test. Exploratory and confirmatory factorial analyses were made using Factor software version 12.03.02. The final tool, iKetoCheck, consists of 10 questions with 5-point Likert scale answers. It evaluates various aspects such as informing caregivers about the diet, organization of meals, measurement of ketosis, weighing food consumed, diet negligence, use of carbohydrate-free medications, attending follow-up visits, reading food labels, consulting an expert for dietary concerns, and cooking at home. The factorial analysis resulted in three factors: “attention,” “organization,” and “precision,” with satisfactory results for indices in exploratory and confirmatory analyses. Although higher mean values of ketonemia measurement were observed in patients with a higher adherence score, these values were not statistically significant (p = 0.284). In conclusion, despite the small sample size, iKetoCheck is a valid tool for evaluating KDTs’ adherence in Italian drug-resistant epilepsy or GLUT1 deficiency patients. It can provide valuable information to improve patient management and optimize the effectiveness of KDTs.